Dissemination of Retinoblastoma Post-Enucleation: Histopathological Risk Factors Review - Rokim, Fitri Setyani (Universitas Airlangga, 2024)
Introduction: Examining the histopathological markers indicative of high risk in retinoblastoma is imperative for evaluating the potential for post-enucleation recurrence and metastatic spread. Purpose: This article seeks to elucidate diverse definitions of high-risk histopathological features in advanced retinoblastoma, which confer susceptibility to recurrence and metastasis following enucleation. Review: Reducing mortality rates associated with retinoblastoma poses a significant clinical challenge. It is well-established that post-laminar optic nerve invasion, extensive choroidal invasion, and scleral invasion are key features commonly observed in advanced retinoblastoma cases requiring enucleation. Conclusion: The presence of these features in advanced retinoblastoma necessitates adjunctive therapeutic interventions to reduce the risk of orbital recurrence or metastatic spread, thereby enhancing patient survival rates.